2016
DOI: 10.1007/s00253-016-7510-z
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Synechococcus elongatus UTEX 2973 for sugar feedstock production

Abstract: It is important to obtain abundant sugar feedstocks economically and sustainably for bio-fermentation industry, especially for producing cheap biofuels and biochemicals. Besides plant biomass, photosynthetic cyanobacteria have also been considered to be potential microbe candidates for sustainable production of carbohydrate feedstocks. As the fastest growing cyanobacterium reported so far, Synechococcus elongatus UTEX 2973 (Syn2973) might have huge potential for bioproduction. In this study, we explored the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 34 publications
2
90
1
Order By: Relevance
“…While much research focuses on engineering cyanobacterial metabolism towards the synthesis of end products (e.g., biofuels), cyanobacteria are also under consideration for the production of carbohydrate feedstocks to support fermentative bioindustrial processes [1]. In this approach, cyanobacterial biomass is processed to provide organic carbon [2–6], or cyanobacterial cells are manipulated to secrete simple fermentable sugars [712]. Multiple groups have recently reported that different cyanobacterial species are capable of secreting soluble sugars in considerable quantities, and continuous production can be sustained over long time periods.…”
Section: Introductionmentioning
confidence: 99%
“…While much research focuses on engineering cyanobacterial metabolism towards the synthesis of end products (e.g., biofuels), cyanobacteria are also under consideration for the production of carbohydrate feedstocks to support fermentative bioindustrial processes [1]. In this approach, cyanobacterial biomass is processed to provide organic carbon [2–6], or cyanobacterial cells are manipulated to secrete simple fermentable sugars [712]. Multiple groups have recently reported that different cyanobacterial species are capable of secreting soluble sugars in considerable quantities, and continuous production can be sustained over long time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fixation can then be coupled to the direct conversion of CO 2 into a wide range of products. Cyanobacteria have been engineered to produce commodities such ethylene1, isoprene2, and sugars34; biofuels such as alkanes5, hydrogen6 and terpenoids7; bioplastics such as polyhydroxybutyrate8; and bioactive compounds such as pharmaceuticals9 and vitamins10. One major hurdle to engineering these production systems is the lack of precise, modern genetic tools that exist for other extensively studied prokaryotes such as Escherichia coli .…”
mentioning
confidence: 99%
“…Redox balance in cyanobacteria is also a key consideration, as photosynthesis can generate an overabundance of reducing equivalents in the absence of sufficient catabolic processes, leading to stunted growth (29). Finally, it is worth considering that some cyanobacterial strains may be better equipped to produce certain types of metabolites due to differences in intracellular metabolite pools or cell physiology (23,(29)(30)(31).…”
Section: General Comments On Metabolic Engineering Of Cyanobacteriamentioning
confidence: 99%
“…Typically, between 5-15% of the fixed carbon is stored via this pathway with the glycogen content reaching 50% under certain growth conditions (31,59). The diurnal lifestyle then mandates that the stored chemical energy is utilized during dark periods akin to that during heterotrophic growth.…”
Section: Tca Cycle-derived Productsmentioning
confidence: 99%
See 1 more Smart Citation